Comparative study of using multi-wall carbon nanotube and two different sizes of cerium oxide nanopowders as fuel additives under various diesel engine conditions. (15th November 2019) - Zhang, Zhichao; Lu, Yiji; Wang, Yaodong; Yu, Xiaoli; Smallbone, Andrew; Dong, Chenxuan; Roskilly, Anthony Paul
Highlights: CeO2 Nano powders and CNT as additives can reduce pollutant emissions. CeO2 in smaller size emits higher CO, NOx and PN but lower HC than the larger size. CNT leads to lower gaseous emissions but higher PN emissions than CeO2 . Comparative tests with and without additives were obtained at various engine conditions. Abstract: This research reports the study of using Cerium oxide (CeO2 ) nano additive with two different sizes (25 nm and 50 nm) blended with standard diesel fuel (DF-Ce25 and DF-Ce50) at various engine speed and load conditions. Moreover, carbon nanotube (CNT) is employed as a single additive (DF-CNT). Results indicate that the in-cylinder pressure of DF-CNT is slightly lower than that of DF under the most conditions due to more heat absorption during the evaporation process. In contrast, the in-cylinder pressure of DF-Ce25 and DF-Ce50 is higher than that of DF at relatively low speed due to the improved fuel spray and faster combustion. In terms of emissions, all fuels with nano-additives are overall lower than DF. DF-CNT can reduce CO, HC, NOx and PN by 20%, 22.6%, 21% and 5.5% respectively compared with DF, due to its improved spray and lower combustion temperature. Meanwhile, DF-Ce25 and DF-Ce50 produce the overall higher level of emissions of CO, NOx and HC than DF-CNT except for PN. A minimum engine (load-speed) limit and a maximum engine limit are found for CO emissions. Furthermore, DF-Ce25 emits higher NOx and lower HC than DF-Ce50, because CeO2 of 25 nm has a higher reaction rate of CeO2 due to its larger surface area and in return hinders the reaction of Ce2 O3 . The difference of PN emissions between the two sizes of CeO2 is the comprehensive result of the oxidization of particulate matters and the aggregation of unburnt fuel.